EFFECTS OF DIGITAL TECHNOLOGY ON LINGUISTICS - Bozorova Zarina Baxriddin qizi (TADQIQOTLAR, 2025)
Annotation. This article explores the multifaceted effects of digital technology on linguistics, focusing on both theoretical and practical implications. It examines how digital tools have influenced language use, language learning, communication styles, and the evolution of new linguistic phenomena such as internet slang and emojis. The study also highlights the role of artificial intelligence, machine translation, and social media  in  shaping  modern  linguistic  landscapes.  Furthermore,  it  discusses  the preservation and digital documentation of endangered languages. Overall, the article provides  insights  into  how  digital  transformation  continues  to  reshape  the  field  of linguistics, opening new opportunities and challenges for researchers, educators, and language users.